2007
DOI: 10.1007/s11801-007-6116-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth interruption on the properties of InGaN/GaN MQWs grown by MOCVD

Abstract: InGaN/GaN MQWs structures were grown by MOCVD. The effects of the growth interruption time on the optical and structural properties of InGaN/GaN MQWs were investigated. The experimental results show that the growth interruption can improve the interface quality, increase the intensity of photoluminescence (PL) and electroluminescence (EL); but if the interruption time was too long, the well thickness and the average In composition of MQWs decreased, and the EL intensity also decreased due to poor interface qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Therefore, in addition to the advantage of offering a better optical confinement in the slab waveguide structure, the In 0.03 Ga 0.97 N WGLs may significantly improve the emission efficiency of the active region. This advantage has also been observed in violet LD structures and in InGaN/GaN MQW structure with the InGaN layer underlying the active regions [12][13][14][15]. EL characteristics of structure D indicate that the LD structure with In 0.03 Ga 0.97 N waveguides will have higher optical gain for lasing.…”
Section: Effect Of Ingan Waveguiding Layersmentioning
confidence: 73%
“…Therefore, in addition to the advantage of offering a better optical confinement in the slab waveguide structure, the In 0.03 Ga 0.97 N WGLs may significantly improve the emission efficiency of the active region. This advantage has also been observed in violet LD structures and in InGaN/GaN MQW structure with the InGaN layer underlying the active regions [12][13][14][15]. EL characteristics of structure D indicate that the LD structure with In 0.03 Ga 0.97 N waveguides will have higher optical gain for lasing.…”
Section: Effect Of Ingan Waveguiding Layersmentioning
confidence: 73%
“…It was previously reported that the InGaN/GaN superlattices may act as strain relief layers. 31) Hence, they will relieve the strain accumulation during the InGaN QD active region growth and be beneficial to indium incorporation by the composition pulling effect. 29,30) The mechanism of EL blue shift may be attributed to the carrier screening by the quantum confined Stark effect (QCSE).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the mechanism for the LED performance improvement by InGaN IL, such as enhanced light output power and decreased operation voltage, is still not clear to date. Strain relaxation [5][6][7][8] and improved current spreading 9,10) were proposed as the main reasons by different research groups. Besides, the superior quality of MQWs resulting from the InGaN IL induced growth-mode change may also play a role in the mechanism.…”
Section: Study Of the Role Of Ingan Ilmentioning
confidence: 99%
“…The reduction of the density of V-shaped defects was also reported. 5,6) Leem et al studied the optimized conditions (indium content, thickness) for InGaN IL or InGaN/ GaN SLs by atomic force microscopy, photoluminescence and peak-wavelength shift as a function of the photoluminescence excitation power, and obtained the best conditions for InGaN IL (3% indium content, 30 nm) and InGaN/GaN SLs (10 pairs, 10% indium content, 2.4 nm/4 nm). 7) With similar consideration, Tsai et al optimized the silicon doping level of In 0:08 Ga 0:92 N/GaN SLs.…”
Section: Introductionmentioning
confidence: 99%